Urban Stock-Demography Approach to Uncover Electric Vehicle Battery and Embedded Lithium Stock across 366 Cities in China - Chenyang Wang; Peng Wang; Linchang Zheng; Wei Chen; Yuqi Hu; Rui Jing; Yi Ding; Xiaojie Liu; Wei-Qiang Chen (Ecosystem Health and Sustainability)
Limited primary lithium resources has urged China to expand the secondary sources through recycling lithium-ion batteries (LIBs) to support its electric passenger vehicles (EPVs) ambitions. However, the lack of detailed geographic data complicates lithium stock measurement and hinders efficient recycling efforts. This study integrates urban demography approach into in-use stock analysis to map the spatial–temporal dynamics of lithium stock in EPVs across 366 Chinese cities from 2010 to 2020. The findings show LIB capacity increased from nearly 0 to 125 GWh in 2020 and in-use lithium stock reached 26.6 kilotons—2.4% of China’s total lithium reserves. Regional disparities persist: around 21 very large and super-large cities hold over 58% of total lithium in-use stock, with eastern regions dominating distribution; smaller cities, despite faster growth, maintain a smaller share. Population size, economic activity, and policy incentives emerge as key drivers, with a U-shaped relationship between per-capita lithium stock and newly introduced stock reflecting market saturation in some areas and policy-driven growth in others. Such high-resolution data can help governments and companies design recycling networks tailored to regional needs, promoting operational efficiency and sustainable lithium supply chains.